The Pocket Guide to Restorative Justice. - Wallis, Pete (Jessica Kingsley Publishers, 2007)
'Restorative justice ... puts the emphasis on repairing the harm caused, holding offenders to account before their victims ... It is not a soft option. It is tough for an offender to continue denying the consequences of their actions when they sit across the table from their victim. This explains why restorative justice is effective in cutting re-offending. Such face-to-face meetings ... can also help the victim.'. - Cherie Booth QC. This pocket-sized guide can be taken conveniently to meetings, interviews and visits, to be used as a quick reference point for information about the.